Self-Reported Physical Activity Is Associated with Lupus Nephritis in Systemic Lupus Erythematosus: Data from KORean Lupus Network (KORNET) Registry - Kim, Seong-Kyu; Choe, Jung-Yoon; Lee, Shin-Seok (Yonsei medical journal, 2018)
The aim of this study was to identify the associations among physical activity, disease activity, and organ damage in patients with systemic lupus erythematosus (SLE). A total of 415 patients with SLE were consecutively enrolled from the KORean lupus Network (KORNET) registry. This registry assessed clinical features, disease activity [Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K)], and organ damage [Systemic Lupus International Collaborating Clinics/American College of Rheumatology (SLICC/ACR) Damage Index (SDI)] upon enrollment in the study. Self-reported physical activity was measured by the International Physical Activity Questionnaire. Statistical analyses were conducted using the Mann-Whitney U test and multivariate logistic regression analysis. A significant difference in vigorous activity was noted between patients with lupus nephritis (LN) (n=93) and those without LN (n=322) (p=0.012), but not in moderate and walking activities. In contrast, no differences in physical activity, walking, moderate, and vigorous intensity, according to SLEDAI-2K and SDI were found. In addition to younger age (p=0.032), high physical component summary of SF-36 (p=0.004) and SLEDAI-2K (p=0.038), and less vigorous physical activity were associated with LN (p=0.024). However, cardiovascular disease was not associated with physical activity in SLE patients. This study showed that patients with LN had less vigorous physical activity than patients without LN. The results suggest that lupus nephritis might be associated with physical activity.